2017
DOI: 10.9734/cjast/2017/34690
|View full text |Cite
|
Sign up to set email alerts
|

Glued laminated Timber Produced with Tropical Brazilian Wood Species

Abstract: Despite the wood versatility, its application is, sometimes, difficult because of its properties and performances under different work conditions are not completely known. The present work, developed in Laboratory of wood and wood structures (known as LaMEM),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Several native species from forest management are not recognized for commercialization as raw or engineered timber due mainly to the lack of research on its properties or the correct dissemination of knowledge. The main studies on Brazilian native species can be found in [2][3][4].…”
Section: Introduction 789mentioning
confidence: 99%
“…Several native species from forest management are not recognized for commercialization as raw or engineered timber due mainly to the lack of research on its properties or the correct dissemination of knowledge. The main studies on Brazilian native species can be found in [2][3][4].…”
Section: Introduction 789mentioning
confidence: 99%
“…Dentre estes, destacam-se painéis Oriented Strand board -OSB (Zhuang et al, 2022), elementos em madeira lamelada colada -MLC (Zangiacomo et al, 2017) e painéis de madeira lamelada colada cruzada, em inglês Cross Laminated Timber -CLT (Brandner et al, 2016).…”
Section: Introductionunclassified